Negotiating academic and coaching identities: A case study of occupational socialization of a Japanese university track and field teacher-coach - Mizushima, J.; Kajitani, R.; Kuki, S. (International Journal of Sports Science & Coaching, 2025)
This case study explores how a Japanese university teacher-coach developed an integrated professional identity encompassing teaching, research, and coaching. Drawing on Occupational Socialization Theory (OST), we examined how the participant—an academic faculty member who also serves as head coach of a competitive collegiate track and field team—made sense of and navigated overlapping institutional, cultural, and interpersonal expectations. Using a life-story methodology and three semi-structured interviews, data were analyzed through collaborative qualitative analysis, which emphasized co-interpretation with the participant and a co-author. Findings were presented across OST's three phases: acculturation, professional socialization, and organizational socialization. The participant's early exposure to teacher-coaches shaped relational and pedagogical foundations, while graduate training and institutional engagement enabled a gradual reframing of coaching as an academic practice. This study contributes to OST by illustrating identity integration as a recursive and culturally situated process. Practical implications highlighted how coach developers and institutions can better support multi-role professionals through mentoring, interdisciplinary collaboration, and structural recognition of coaching labor. The case also offers coaching-specific insights into balancing roles, applying research to training, and adapting to institutional demands and provides guidance for university teacher-coaches navigating identity complexity in similar high-performance university settings.